Small business and welfare reform: Levy Institute Survey of hiring and employment practices - Oren M. Levin-Waldman (Levy Economics Institute of Bard College, 1999)
The Levy Institute conducted a survey of small businesses to elicit information about their hiring and employment practices, especially the hiring of former welfare recipients; preferences regarding education, training, and other characteristics of potential employees; effects of increases in the minimum wage on employment decisions; and their responses to various forms of government wage and training subsidies. Analysis of the survey results indicates weaknesses in the assumptions on which recent welfare reform has been based. It also suggests a role for small business that has been overlooked. An active partnership between government and small business, involving incentives for hiring and training as well as mandates for welfare reduction, is required if former welfare recipients are to become independent and productive members of the labor force.
Keywords: 330